My heart belongs here: an investigation into the predictive role of destination psychological ownership on tourism ethnocentrism - David Amani; Betty Begashe; Esther Ernest Mfumbilwa (Cogent Social Sciences)
Tourism destinations worldwide are endeavoring to enhance local residents’ support for the domestic tourism economy by fostering a positive bias. Extensive literature highlights the prevalent concern of local resident support for domestic tourism, particularly in developing countries. Although empirical testing in this area is limited, theoretical postulations suggest that despite the side effects of the tourism sector, local residents who experience the social and economic impacts of tourism tend to exhibit a favorable bias towards their own tourism destination. This bias is widely recognized as a significant factor shaping their behavior. This study builds upon previous research in marketing and psychology to investigate the drivers of tourism ethnocentrism in emerging tourism destinations, with Tanzania serving as a case study. The conceptual model of the study explores the role of destination psychological ownership as a driver of tourism ethnocentrism, mediated by destination brand patriotism. Data were collected from 357 local residents in Tanzania and analyzed using structural equation modeling. The findings reveal that destination psychological ownership significantly influences tourism ethnocentrism through destination brand patriotism. These results suggest that tourism ethnocentrism emerges when individuals develop a sense of ownership, which fosters patriotism and, consequently, an intention to support the domestic tourism economy.